Immunosuppressive Property of MSCs Mediated by Cell Surface Receptors - Liu, Siyu; Liu, Fei; Zhou, You; Jin, Baeku; Sun, Qiang; Guo, Shu (Frontiers in Immunology, 2020)
In the past decade, mesenchymal stem cells (MSCs) tend to exhibit inherent tropism for refractory inflammatory diseases and engineered MSCs have appeared on the market as therapeutic agents. Recently, engineered MSCs target to cell surface molecules on immune cells has been a new strategy to improve MSC applications. In this review, we discuss the roles of multiple receptors (ICAM-1, Gal-9, PD-L1, TIGIT, CD200 and CXCR4) in the process of MSCs’ immunosuppressive properties. Furthermore, we discuss the principles and strategies for developing receptor-regulated MSCs and their mechanisms of action and the challenges of using MSCs as immunosuppressive therapies.